Bone regeneration of demineralized dentin matrix with platelet-rich fibrin and recombinant human bone morphogenetic protein-2 on the bone defects in rabbit calvaria - Beom-Jin Kim; Seok-Kon Kim; Jae-Hoon Lee (SpringerOpen, 2021)
Abstract Background This study was to evaluate the bone formation ability of demineralized dentin matrix (DDM) combined with platelet-rich fibrinogen (PRF) and DDM combined with recombinant human bone morphogenetic protein-2 (rhBMP-2) to improve the osteoinductive ability of DDM. Methods After four bone defects with a diameter of 8mm were created in the calvarium of each rabbit, DDM was grafted into the first defect (experimental groups 1), a combination of DDM and PRF was grafted into the second defect (experimental groups 2), and DDM with absorbed rhBMP-2 was grafted into the third defect (experimental groups 3). The fourth defect was used as the control group. Twelve healthy male rabbits (New Zealand, white rabbits) weighing around 3.0-4.0 kg were used. Among 12 rabbits, 3 rabbits were sacrificed immediately after surgery and at 2, 4, and 8 weeks after surgery, respectively. Histopathologic analysis and histomorphometric analysis were conducted to evaluate bone formation in each group. Results The PRF/DDM group did not show a significantly higher degree of new bone formation in calvarial bone defects than the DDM group at 2, 4, and 8 weeks postoperatively in histopathological findings and histomorphometric results. On the other side, the rhBMP-2/DDM group showed higher degrees of new bone formation and calcification, and the lamellae of bone matrix, which are observed in mature bone tissue, were more distinctly visible in the rhBMP-2/DDM group. Moreover, the rhBMP-2/DDM group showed a significantly higher amount of new bone formation, compared to the DDM group at 4 and 8 weeks postoperatively (P<0.05) in histomorphometric results. Conclusion The DDM has great potential as a carrier for the maintenance and sustained release of rhBMP-2, which has been recently receiving wide attention as a type of signaling molecules to promote bone formation.